Discourses of Development, Right and Responsibility: Right to Water in Assam: Challenging State Rights: The Discourse of Right to Water in Assam (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In the recent past, there have been vociferous claims for considering right to water as a basic human right. There have been apprehensions as to whether the excessive interest in our ‘rights’ over water could lead to exhaustion or evaporation of this precious little natural gift through over appropriation. But the discourses of human right in general and that of water in particular are often seen to have challenged some of the rights and responsibilities of the modern states that are supposed to take care of the rights of the people in the form of national rights and national interest. This paper analyses how the right of people to enjoy and appropriate water has been of utmost relevance these days in the midst of large-scale environmental degradation and over-exploitation of the resources for commercial purposes at the cost of the people who have a legitimate claim over the same with special reference to Assam. It focuses on the state-wide movement undertaken in Assam by the newly formed organization, Krishak Mukti Sangram Samiti seeking to establish people’s right over all forms of natural resources with special emphasis on water. This movement has strong significance in the context of the already continuing movement against implementation of some hydroelectric power projects that are likely to disturb the right to life for many of the people of Assam. As an ecological study, this paper studies some of the relevant literature, specifically the collection of articles written by Akkhil Gogoi on big dams to support the thesis that the discourse of human right over water is here to challenge some of the rights of the ‘state’ over the natural resources.